2020
DOI: 10.1186/s13018-020-01622-9
|View full text |Cite
|
Sign up to set email alerts
|

Treating AO/OTA 44B lateral malleolar fracture in patients over 50 years of age: periarticular locking plate versus non-locking plate

Abstract: Background: The role of locking plate in lateral malleolar fracture fixation for the elderly remains unclear. The aim of our study is to compare radiological and functional outcomes in older patients (> 50 years) with AO/OTA 44B lateral malleolar fractures after locking plate (PLP) or one-third non-locking tubular plate (TP) lateral fixation. Methods: We retrospectively reviewed the medical records of 72 patients (PLP group, 34 patients; TP group, 38 patients; mean age, 61.9 ± 7.6 years; range, 51-80 years; fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…Regarding the FAOS, our study shows excellent results in the clinical control after 12 months comparable to those described by Shih et al [ 57 ].…”
Section: Discussionsupporting
confidence: 88%
“…Regarding the FAOS, our study shows excellent results in the clinical control after 12 months comparable to those described by Shih et al [ 57 ].…”
Section: Discussionsupporting
confidence: 88%
“…Eleven studies were considered suitable for inclusion in this systematic review and meta-analysis. 4,7,8,11,12,17,20,21,25,26,28 Ten of the included studies were retrospective cohort studies. 4,7,8,11,12,17,20,21,25,26 One of the included studies was a randomized controlled trial.…”
Section: Searchmentioning
confidence: 99%
“…Of all included studies, 4 (36%) measured the functional outcome of the ankle in patients. 4,11,12,26 Different functional outcome measure tools were used: Shih et al 26 used the Foot and Ankle Outcome Score (FAOS), Bilgetekin et al 4 and Herrera-Pérez et al 11 used the American Orthopaedic Foot & Ankle Society (AOFAS) score), and Huang et al 12 used both the Olerud Molander Score (OMS) and the AOFAS score. The follow-up time at which the AOFAS score had been measured was not reported by Bilgetekin et al 4 All other studies reported results on the long term (ie, after 6 months), Herrera-Pérez et al 11 was the only study that reported both short-term (ie, less than 6 months) and longterm scores (Table 2).…”
Section: Functional Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…However, in clinical application, the application effect of the above 2 kinds of internal fixation treatment is still controversial. [ 3 , 4 ] Therefore, this study further compared and analyzed the application effect of AO mini-plate screw and KW fixation in the treatment of metacarpal fracture, which is reported as follows.…”
Section: Introductionmentioning
confidence: 99%